FEKTIFITAS MANAJEMEN WAKTU BAGI MAHASISWA UNTUK MENINGKATKAN TARGET AKADEMIS PADA POLITEKNIK NEGERI SRIWIJAYA - Ummasyroh Ummasyroh; Dewi Fadila; Yusleli Herawati (Politeknik Negeri Sriwijaya, 2013)
This study aims to determine the effectiveness of time management for State Polytechnic of Sriwijaya’s students to improve their time management ability in order to achieve academics targets and increase the effectiveness of the Academic Supervisor in evaluating of students successful the end of semester. The study involved 97 respondents were selected by using Proportional Random Sampling. Measurement accuracy in time management by students and academic accuracy in target index score indicates strong. It means that the students can use their time effectively. Relationship between the obstacles faced by the accuracy of managing time is -0.301. Relationship between the barriers faced by academic target accuracy is -0.289, which means that the precise of the student conduct the academic targets the smaller barriers to be faced. Time independent study conducted by the student has not obtained the ideal self-study time. As 59.8% of respondents allocate self study time for 1-2 hours/day, it is necessary to increase the role of faculty and the Academic Advisor to constantly remind students to consistently perform a minimum of six hours of independent study per day and accumulated self-learning can be reached 36 hours a week and improve time management skills and establish a vision of life through activities such as training Life Management and Managing Future Time, so the student’s life target can be planned earlier.